Analisis Yuridis Kepemilikan Hak Atas Tanah Ulayat Berdasarkan Putusan Perkara Perdata Nomor: 13/Pdt.G/2021/Pn End - Maria Angelica Dei Nai; Agustinus Hedewata; Husni Kusuma Dinata (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this study is to analyze the juridical ownership of customary land rights based on the decision of civil case Number: 13/Pdt.G/2021/Pn End. The type of research used by the author is Normative Legal research. The sources of legal materials used in this research are primary, secondary and tertiary legal materials. The method of processing legal materials through 4 (four) stages, namely identification of legal materials, inventory of legal materials, verification of legal materials and interpretation of legal materials which are then analyzed descriptively qualitatively. Based on the research results, the Plaintiff was unable to prove that the disputed object was his property and vice versa the Defendants were unable to prove that the disputed object was customary land belonging to the Kila Da Tribe. This is because there are inconsistencies regarding the structure, hierarchy, and mechanism of worship in the Customary Law Community that differ in the evidence of the Plaintiff and the Defendants. The Plaintiffs and Defendants were also unable to prove recognition by executive agencies regarding ownership of the disputed object. In addition, the Plaintiff was unable to prove that he was a legitimate heir as stipulated in Article 832 of the Civil Code. Likewise, the Defendants were unable to prove that they were the legitimate heirs of Kila Da from Wednesday Kila's descendants. The author argues that the consideration of the Panel of Judges in giving a decision in this case was correct, by rejecting the Plaintiff's claim in its entirety. Because all the arguments of the lawsuit regarding ownership of rights to customary land, cannot be proven by the Plaintiff.